Microorganisms in Whole Botanical Fermented Foods Survive Processing and Simulated Digestion to Affect Gut Microbiota Composition - Chan, Miin; Liu, Di; Wu, Yingying; Yang, Fan; Howell, Kate (Frontiers in Microbiology, 2021)
Botanical fermented foods have been shown to improve human health, based on the activity of potentially beneficial LAB and yeasts and their metabolic outputs. However, few studies have explored the effects of prolonged storage and functional spices on microbial viability of whole fermented foods from fermentation to digestion. Even fewer have assessed their impact on the gut microbiota. Our study investigated the effects of production processes on LAB and yeast microbial viability and gut microbiota composition. We achieved this by using physicochemical assessments and an in vitro gastrointestinal and a porcine gut microbiota model. In low-salt sauerkraut, we assessed the effects of salt concentration, starter cultures and prolonged storage; in tibicos, prolonged storage and the addition of spices cayenne, ginger and turmeric. In both food matrices, LAB counts significantly increased (P<0.05), reaching a peak of 7 to 8 log cfu/g, declining to 1 to 1.5 log cfu/g by day 96. Yeast viability remained at 5 to 6 log cfu/g in tibicos. Ginger tibicos had significantly increased LAB and yeast viability during fermentation and storage (P<0.05). For maximum microbial consumption, tibicos should be consumed within 28 days; sauerkraut, seven weeks. Simulated upper GI digestion of both products resulted in high microbial survival rates of 70 to 80%. The 82% microbial survival rate of cayenne tibicos was significantly higher than other treatments (P<0.05). 16S rRNA sequencing of simulated porcine colonic microbiota showed that both spontaneously fermented sauerkraut and tibicos increase the relative abundance of Megasphaera 85-fold. These findings will inform researchers, producers and consumers about the factors that affect the microbial content of fermented foods, and their potential effects on the gut.